Organic aerosol composition and sources in Pasadena, California, during the 2010 CalNex campaign. Issue 16 (29th August 2013) - Hayes, P. L.; Ortega, A. M.; Cubison, M. J.; Froyd, K. D.; Zhao, Y.; Cliff, S. S.; Hu, W. W.; Toohey, D. W.; Flynn, J. H.; Lefer, B. L.; Grossberg, N.; Alvarez, S.; et al.
Abstract : [1] Organic aerosols (OA) in Pasadena are characterized using multiple measurements from the California Research at the Nexus of Air Quality and Climate Change (CalNex) campaign. Five OA components are identified using positive matrix factorization including hydrocarbon‐like OA (HOA) and two types of oxygenated OA (OOA). The Pasadena OA elemental composition when plotted as H : C versus O : C follows a line less steep than that observed for Riverside, CA. The OOA components from both locations follow a common line, however, indicating similar secondary organic aerosol (SOA) oxidation chemistry at the two sites such as fragmentation reactions leading to acid formation. In addition to the similar evolution of elemental composition, the dependence of SOA concentration on photochemical age displays quantitatively the same trends across several North American urban sites. First, the OA/ΔCO values for Pasadena increase with photochemical age exhibiting a slope identical to or slightly higher than those for Mexico City and the northeastern United States. Second, the ratios of OOA to odd‐oxygen (a photochemical oxidation marker) for Pasadena, Mexico City, and Riverside are similar, suggesting a proportional relationship between SOA and odd‐oxygen formation rates. Weekly cycles of the OA components are examined as well. HOA exhibits lower concentrations on Sundays versus weekdays, and the decrease in HOA matches that predicted for primary vehicle emissions using fuel sales data, traffic counts, and vehicle emission ratios. OOA does not display a weekly cycle—after accounting for differences in photochemical aging —which suggests the dominance of gasoline emissions in SOA formation under the assumption that most urban SOA precursors are from motor vehicles. Key Points: For the same photochemical ages, SOA to CO ratios do not display a weekly cycle Organic aerosol is apportioned into five components using PMF SOA formation/evolution is similar for several urban locations